A retrospective cohort study of race/ethnicity, pre-pregnancy weight, and pregnancy complications. (12th December 2022) - Tiwari, Ruchi; Enquobahrie, Daniel A.; Wander, Pandora L.; Painter, Ian; Souter, Vivienne
Abstract: Objective: To examine the relationship between race/ethnicity, pre-pregnancy overweight/obesity status, and pregnancy complications. Methods: We conducted a retrospective cohort study among mothers with singleton live births using data from hospitals contributing to the Obstetrical Care Outcomes Assessment Program database ( N  = 72, 697). Race was categorized as Non-Hispanic (NH) White, NH African-American, Hispanic, NH Asian, NH American Indian/Alaskan Native, and NH Native-Hawaiian/Other Pacific Islander. Pre-pregnancy overweight/obesity status was defined as body mass index (BMI)≥25 kg/m 2 . Pregnancy complications evaluated were gestational diabetes, pre-eclampsia, and cesarean delivery. We fitted adjusted and unadjusted stratified Poisson regression models with robust standard errors. Interaction terms were used to assess statistical significance of interactions between race/ethnicity and pre-pregnancy overweight/obesity status. Results: Most women were NH White (52.1%) and more than half had overweight/obesity (54.3%). Among women with overweight/obesity, Hispanics had a lower risk of cesarean delivery as compared to NH White (adjusted relative risk, aRR:0.89; 95%CI:0.84–0.93). Similarly, among women with overweight/obesity, Hispanic and NH Native-Hawaiian/Other Pacific Islander had a lower risk of preeclampsia (aRR:0.74; 95%CI:0.66–0.82 and aRR:0.64; 95%CI:0.44–0.92, respectively) and NH African-American had a greater risk of gestational diabetes (aRR:1.23; 95%CI:1.07–1.42) when compared with NH White women. These associations were not present among normal-weight women. Women with overweight/obesity, when compared with women of normal-weight, had an increased risk of gestational diabetes and cesarean delivery among all race/ethnicities except NH American Indian/Alaskan Native and NH Native-Hawaiian/Other Pacific Islander, respectively ( p -values < .05). The multiplicative interaction terms between race/ethnicity and overweight/obesity status were significant for all three complications (interaction p -values < .05). Conclusion: Pre-pregnancy overweight/obesity status modifies associations of race/ethnicity with pregnancy complications. Conversely, race/ethnicity modifies associations of pre-pregnancy overweight/obesity status with pregnancy complications. Our findings have implications for public health and clinical practice, supporting the focus on healthy preconception weight and risk stratification across racial/ethnic groups.